HUBUNGAN MANAJEMEN WAKTU DENGAN KEBIASAAN PROKRASTINASI PENYUSUNAN SKRIPSI MAHASISWA KEPERAWATAN ANGKATAN VIII STIKES BINA USADA BALI - Hakim, Nina Rismawati; Prihandhani, IGAA Sherlyna; Wirajaya, I Gede (LP2M IKIP PGRI Bali, 2018)
Time management plays a role in the completion of student academic tasks well. The inability of students in time management leads them to tend to delay doing their academic tasks. The delay in doing these academic tasks is called